Oral and Dental Abnormalities Caused by a Pediatric Rhabdomyosarcoma Tumor Treatment: A Clinical Case Report - Luísa Bandeira Lopes; Rodrigo Themudo; João Botelho; Vanessa Machado (MDPI AG, 2020)
Rhabdomyosarcoma is one of the most common soft-tissue sarcomas in children. The therapy for this condition has evolved significantly over recent decades, as has survival rates. Nevertheless, multiagent chemotherapy, radiation therapy, surgical resection or a combination of these modalities still have to be performed. This case report presents a 16-year-old boy with oral and dental effects after rhabdomyosarcoma treatment, diagnosed at the age of 4 years old. This report highlights the key role of dentists in the clinical management of rhabdomyosarcoma cases before, during and after treatment, and its potential side effects.